Characteristics of the internal flow and the near-field spray of a single-hole injector and a multi-hole injector for diesel engines. (April 2016) - Dong, Pengbo; Inaba, Takuya; Nishida, Keiya; Shimo, Daisuke
The geometric structure of a diesel fuel injector plays a significant role in the injected spray behaviours. Furthermore, the characteristics of diesel fuel spray are well known to have a crucial impact on the combustion process and the resulting engine performance. A single-hole diesel injector is usually applied in fundamental internal flow, spray and combustion research. On the contrary, under most realistic operating conditions, an axisymmetric multi-hole injector is used to couple with the combustion chamber. In the present paper, a detailed experimental investigation of the diesel fuel spray emerging from a single-hole nozzle and a multi-hole nozzle and a computational study of the internal flow inside these two kinds of configuration are reported. Globally, the analysis mainly focused on the different injection processes (the injection rate) and the spray structures of the single-hole nozzle and the multi-hole nozzle, keeping the same sac configuration, the same nozzle hole diameter of 0.1 mm and the same hole length of 0.8 mm for an injection quantity of 2 mm 3 per hole. High-speed images of the spray development were freeze captured by Mie scattering at 10, 000 frames/s under the conditions where the rail pressure varies from 80 to 180 MPa, the ambient pressure is 1.5 MPa, the room temperature T  = 298 K and there is an air environment. Image-processing algorithms were used to determine the fuel spray characteristics. The experimental results revealed that the spray of a multi-hole nozzle with 10 holes had a longer injection duration, a lower injection rate, a shorter spray tip penetration, a wider spray angle and a wider spray cone angle than those of a single-hole nozzle. The spray behaviours of the multi-hole nozzle were more sensitive to variation in the pressure than those of the single-hole nozzle. Moreover, aiming to correlate the observed spray properties to the internal flow phenomenon, computational fluid dynamics simulations were also carried out under the baseline conditions. The more complicated internal flow inside the multi-hole nozzle provided added insight into the different spray characteristics for these two nozzles.